Geographic variation in health system performance in rural areas of New South Wales, Australia. (10th February 2021) - Slimings, Claudia; Moore, Malcolm
Abstract: Objectives: (i) To quantify geographic variation in selected health system performance indicators across local government areas of rural New South Wales and (ii) to compare relationships between sociodemographic factors and health system performance indicators across the regions. Design: Ecological study. Setting: Rural New South Wales communities. Participants: Eighty‐nine local government areas in rural areas comprising 47 inner regional, 33 outer regional, 6 remote and 3 very remote areas. Main outcome measures: Deaths from avoidable causes, public hospital admissions for potentially preventable conditions, screening program participation, immunisation coverage. Results: The largest geographic variation between rural areas of New South Wales was seen for avoidable mortality and potentially preventable hospital admissions. The average annual avoidable age‐standardised mortality rate (2013‐2017) ranged from 78.1 per 100 000 population to 493.7 per 100 000 population and the age‐standardised rate of potentially preventable hospitalisations (2016‐2017) ranged from 1491 to 5797 per 100 000 population. Approximately three quarters of local government areas had bowel and breast cancer screening participation rates equivalent to or better than the overall New South Wales rate; however, only 34% of local government areas met the New South Wales rate for cervical cancer screening. The least variation was seen for immunisation coverage; Byron had the lowest immunisation coverage for all 3 ages. The most common explanations for variation between rural local government areas in New South Wales were remoteness and socioeconomic characteristics. Conclusions: The analysis of health system performance indicators reveals differences among New South Wales rural local government areas. The results highlight specific areas that might benefit from targeted intervention to improve inequities particularly for avoidable mortality and potentially preventable hospitalisations.